Types and Symbolic Meanings of Food in the Cupu Panjala Tradition in Gunungkidul - Amanda Pisan Pramesti; Budi Waluyo; Winda Dwi Lestari; Kenfitria Diah Wijayanti; Astiana Ajeng Rahadini; Favorita Kurwidaria; Tya Resta Fitriana; Prima Veronika (Faculty of Humanities, Universitas Jenderal Soedirman, 2025)
Tradition is one of the customs of society that has been passed down from generation to generation and is still preserved by people who consider that existing methods are the most correct. This research produces types and symbolic meanings of food in the Cupu Panjala Gunungkidul Tradition. This research was analyzed using Roland Barthes' semiotic approach with qualitative descriptive methods. The data that is the object of this research is ubarampe food (offerings) in the Cupu Panjala Tradition. Data sources in this research consist of informants, events and documents. The sampling technique in this research uses a purposive sampling technique to collect the required data. The data collection process in this research was carried out by means of observation, interviews and document analysis. The validity test used in this research uses data source triangulation and theory triangulation. The data analysis technique in this research uses the Miles and Huberman technique which consists of collecting data, reducing data, presenting data, and drawing conclusions. Based on this research, symbolic meaning itself is divided into three, namely denotation, connotation and myth.